Factors influencing family support and family burden in caring for family members with a history of violent behavior: A systematic review - Andre Soares Dos Santos; Dwi Heppy Rochmawati; Wahyu Endang Setyowati (School of Health Sciences Al-Ma'arif, 2026)
Background: Family caregivers play a central role in caring for relatives with severe mental illness, particularly those with a history of violent behavior. In this context, caregivers are required to provide continuous supervision, emotional support, and practical assistance, while also managing fear, stigma, and prolonged caregiving demands. These conditions may influence both family support and family burden through a complex interaction of clinical, psychosocial, and structural factors. Objective: This study aimed to systematically identify, analyze, and synthesize the factors influencing family support and family burden in caring for family members with a history of violent behavior. Methods: This study employed a systematic review design. A comprehensive literature search was conducted in PubMed, Scopus, ProQuest, SAGE Journals, and ClinicalKey for Nursing for studies published between 2015 and 2025. Quantitative, qualitative, and mixed-method studies were included if they examined determinants of family support or caregiver burden among family caregivers of individuals with severe mental illness involving aggression or a history of violent behavior. Study selection, data extraction, and methodological quality appraisal were conducted independently by two reviewers using standardized procedures and the Joanna Briggs Institute critical appraisal tools. Results: Ten studies met the inclusion criteria. The review identified three major domains influencing family support and family burden: clinical factors, psychosocial factors, and structural factors. Patient aggression, symptom severity, relapse, and poor social functioning consistently increased caregiver burden. Psychosocial factors, particularly affiliated stigma, emotional distress, gendered caregiving roles, and family relationship patterns, further intensified burden and reduced caregiving resilience. Structural barriers, including limited access to mental health services, weak care coordination, insufficient caregiver involvement in decision-making, and economic hardship, also weakened family support capacity. Intervention evidence suggested that family psychoeducation and structured support may reduce caregiver burden, although their effectiveness varied across contexts. Conclusion: Family support and family burden in the care of relatives with a history of violent behavior are shaped by interrelated clinical, psychosocial, and structural determinants. Family-centered and context-sensitive mental health interventions are needed to reduce caregiver burden and strengthen sustainable family support.